Предмет: Алгебра, автор: Nikolya1729

пожалуйста хоть это помогите

Приложения:

Ответы

Автор ответа: m11m
0
1) 27^(-²/₃) +81^(³/₄) +(0.25)⁻² =
  = (3³)^(-²/₃) +(3⁴)^(³/₄) +(¹/₄)⁻² =
  =3⁻² + 3³ + 4² =
  = ¹/₉ + 27 +16 =
  = 43 ¹/₉

2) (         x² +y²          -        x+y       )  xy⁻¹ =
    ( xy^(¹/₂)+x^(³/₂)      y^(¹/₂)+x^(¹/₂) )
=(         x² +y²          -       x(x+y)         )      *  x  =
  ( x(y^(¹/₂)+x^(¹/₂))      x(y^(¹/₂)+x^(¹/₂)) )      y
=     x² +y² -x² -xy    *   x  =
    x(y^(¹/₂) +x^(¹/₂))       y
=           y(y-x)           =
   y(y^(¹/₂) + x^(¹/₂))
= (y^(¹/₂) - x^(¹/₂))(y^(¹/₂)+x^(¹/₂)) =
                y^(¹/₂) + x^(¹/₂)
= y^(¹/₂) - x^(¹/₂) = √y - √x
Похожие вопросы
Предмет: Физика, автор: nasveta7783